Pekerjaan Pondasi Tiang Pancang: Cara Pemancangan, Kendala dan Teknologi Terbaru - Nurdiani, Nina (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The foundation work a building project is commonly done when students conducted Real Estate Internship which leads to inadequate knowledge of foundation work obtained during internship, especially the pile foundation work. Related to this condition it is necessary to study the technical specifications of a pile foundation commonly used on a project, how to pile, problems encountered at the field, and the latest technology to reduce obstacles at the field. The study is conducted with a descriptive approach towards building projects in Jakarta built in 2008, when the latest technology of pile foundation came to Indonesia. The results of the study provide knowledge that the pile foundation is made of hard wood, concrete and steel. The form of pile foundations is generally triangular or rectangular. Many building projects use concrete pile foundation with steel reinforcement and spiral reinforcement. The advantages of using concrete pile foundation are in order to be efficient, convenient and practical. Piling foundation uses a drop hammer or jacked piling system to the hardground. Obstacles encountered in the field are the soft soil conditions, the former marsh or land fill. Hydraulic Static Pile Driver (HSPD) or 'Press in Pile' is the latest method as a solution to pile the piling foundation in dense residential neighborhood. This technique can reduce or even eliminate the effects that interfere with the environment (vibration, air pollution and noise pollution) when piling the pile foundation. In general, the technology ‘Press in Pile’ reduces environmental problems as well as provides more convenient, faster and economical effects.